Analytical review on competitive priorities for operations under manufacturing firms - M. Prabhu; Thangasamy Nambirajan; Nabaz Nawzad Abdullah (Journal of Industrial Engineering and Management (JIEM), 2020)
Purpose: To developed and introduced a measurement scale that may be useful to assess the competitive priorities practices in the manufacturing industries. The objective is to investigate the competitive priorities domains' implementation and its defining measurement items emphasizing manufacturing industries in the Union Territory of Puducherry. Design/methodology/approach: The essential information has been gathered from 350 manufacturing firms by utilizing very much stretchered polls; most part of the data was gathered from best dimension working people like Operations Managers, General Managers and Directors. For analyzing the data the researchers used SPSS and LISREL 8.72 software packages. To find out the result the researchers applied Confirmatory Factor Analysis in this research work. Findings: From the six domains analyzed the result shows that Delivery plays an important role as it occupies the first rank among the domains in competitive priority. Next to Delivery, the majority of the firms fasten more importance to Quality as it ranks second. Cost is ranked as third, while Know-how is ranked as fourth, Flexibility is ranked as fifth and Customer Focus is ranked as sixth. Practical implications: Based on the existing recommendations on scale development literature, authors developed the measurement scale. This measurement scale is helpful for both academicians and practitioners. In this research work authors used the measurement scale to measure the competitive priorities domains. Originality/value: The research paper explains about the manufacturing industries situated in Union Territory of Puducherry. The researchers developed the measurement instrument of competitive priorities practices based on six domains namely quality, cost, delivery, flexibility, customer focus, and know-how. This research work gives innovative literature by recommendations and validating a measurement scale for the competitive priorities. The result reveals that the manufacturing enterprises in the Union Territory of Puducherry.
Keywords: 650; Competitive priorities; quality; cost; manufacturing; confirmatory factor analysis